Menelusuri akar peradaban melayu dalam kepimpinan Abdullah Badawi: Hubungan dua hala Malaysia – China - Mohamad Ikhram Mohamad Ridzuan; Dg Junaidah Awang Jambol; Diana Peters (Academy of Malay Studies, 2025)
This article analyzes Abdullah Ahmad Badawi's leadership in Malaysia's foreign policy towards China through a pragmatic diplomatic approach grounded in Malay civilizational values. The study argues that while Abdullah maintained the continuity of close bilateral ties initiated by Mahathir Mohamad, he also introduced a new approach that was more moderate, harmonious, and reflective of Malay characteristics, emphasizing consultation (musyawarah) and balance in policy decision-making. Accordingly, this study adopts a qualitative approach through a combination of literature review and semi-structured interviews to examine the implementation of Abdullah’s foreign policy across three levels of analysis commonly used in the field of international relations: international, domestic, and individual. The findings indicate that Abdullah’s leadership succeeded in strengthening Malaysia–China bilateral relations not only in economic terms, but also in socio-cultural and security dimensions. His initiatives through platforms such as the East Asia Summit and the promotion of the global halal industry demonstrated Malaysia’s commitment to building stronger regional synergy with China. Furthermore, the study reveals that Abdullah’s modest personality, and his background rooted in Malay civilizational values served as a crucial foundation in shaping a more credible and stable diplomatic posture at the regional level. This study contributes to the discourse on the importance of local cultural elements in shaping the foreign policy of small states and reinforces the significance of leadership personality in international relations. The implications of the study provide deeper insight into how traditional values can be strategically embedded within the increasingly complex international political environment. Future research is recommended to compare Abdullah’s diplomatic approach with that of his successors, particularly in the post–Belt and Road Initiative context and in the evolving dynamics of ASEAN–China relations.